Influence of organic additives on the behaviour of zinc electroplating from alkaline cyanide-free electrolyte - Pary, Paola (2017)
Two similar polymeric organic compounds from the polyquaternium family were studied as levelling additives in an alkaline cyanide-free zinc plating electrolyte. One additive (LA) has amide bonds between its monomers and the other (LU) has urea unions in its chemical structure. Copper cementation on zinc and gas evolution during aging of the zinc coatings were used to evaluate the effect of the chemical structure of the organic additives on the characteristic deleterious aging process of the coatings when electrodeposited with LA. Scanning electron microscopy and X-ray diffraction were used to follow surface morphology and crystallographic modifications of the coatings during aging. Faster copper cementation kinetics, zinc whiskers growth, blistering of the coating and N2, CH4, CO2and H2evolution were observed during accelerated aging of the coatings when LA was used. The coatings produced with LU did not show any aging effect. These studies show the strong influence that subtle changes in the chemical structure of the organic additive may have on the performance of zinc coating during storage.